Changes of MicroRNA Profile and MicroRNA‐mRNA Regulatory Network in Bones of Ovariectomized Mice. (March 2014) - An, Jee Hyun; Ohn, Jung Hun; Song, Jung Ah; Yang, Jae‐Yeon; Park, Hyojung; Choi, Hyung Jin; Kim, Sang Wan; Kim, Seong Yeon; Park, Woog‐Yang; Shin, Chan Soo
ABSTRACT Growing evidence shows the possibility of a role of microRNAs (miRNA) in regulating bone mass. We investigated the change of miRNAs and mRNA expression profiles in bone tissue in an ovariectomized mice model and evaluated the regulatory mechanism of bone mass mediated by miRNAs in an estrogen‐deficiency state. Eight‐week‐old female C3H/HeJ mice underwent ovariectomy (OVX) or sham operation (Sham‐op), and their femur and tibia were harvested to extract total bone RNAs after 4 weeks for microarray analysis. Eight miRNAs (miR‐127, ‐133a, ‐133a*, ‐133b, ‐136, ‐206, ‐378, ‐378*) were identified to be upregulated after OVX, whereas one miRNA (miR‐204) was downregulated. Concomitant analysis of mRNA microarray revealed that 658 genes were differentially expressed between OVX and Sham‐op mice. Target prediction of differentially expressed miRNAs identified potential targets, and integrative analysis using the mRNA microarray results showed that PPARγ and CREB pathways are activated in skeletal tissues after ovariectomy. Among the potential candidates of miRNA, we further studied the role of miR‐127 in vitro, which exhibited the greatest changes after OVX. We also studied the effects of miR‐136, which has not been studied in the context of bone mass regulation. Transfection of miR‐127 inhibitor has enhanced osteoblastic differentiation in UAMS‐32 cells as measured by alkaline phosphatase activities and mRNA expression of osteoblast‐specific genes, whereas miR‐136 precursor has inhibited osteoblastic differentiation. Furthermore, transfection of both miR‐127 and miR‐136 inhibitors enhanced the osteocyte‐like morphological changes and survival in MLO‐Y4 cells, whereas precursors of miR‐127 and ‐136 have aggravated dexamethasone‐induced cell death. Both of the precursors enhanced osteoclastic differentiation in bone marrow macrophages, indicating that both miR‐127 and ‐136 are negatively regulating bone mass. Taken together, these results suggest a novel insight into the association between distinct miRNAs expression and their possible role through regulatory network with mRNAs in the pathogenesis of estrogen deficiency–induced osteoporosis. © 2014 American Society for Bone and Mineral Research.